Pemberdayaan Ekonomi Masyarakat Melalui Pelatihan Produksi Detergen Ramah Lingkungan dan Pemasaran Digital - Tatbita Titin Suhariyanto; Hayati Mukti Asih; Muhammad Faishal (Universitas Pahlawan Tuanku Tambusai, 2023)
The Kamulyan Garbage Bank is located in the Brontokusuman Village RW 20-22, Mergangsan District, Yogyakarta City which is around the Code River. Not a few people throw away the water for washing clothes in the river, thereby disrupting the aquatic ecosystem. This is the reason and objective of this community service program, which is to reduce the impact of river pollution and empower the people around Kali Code. The implementation method is carried out through seminar and practice of using environmentally friendly detergent production equipment, seminar and practice of standard operating procedures (SOP) using production tools, seminar and practice of calculating the cost of production (HPP), as well as seminar and advanced digital marketing practices. This program is in accordance with the UAD Community Service Program roadmap for 2020-2045 which refers to the realization of accelerated marginal areas towards smart, healthy, environmentally friendly areas with socio-entrepreneurship characteristics, universal values and Islam in 2020-2045. Based on the results of the questionnaire, as many as 90% of participants experienced an increase in knowledge after seminar and practicing.